The Effect of Compensation and Career Development on the Quality of Work Life in Nurses at Syiah Kuala University Teaching Hospital - Desi Ismayanti; A. Rohendi; Rinawati Rinawati (CV. Civiliza Publishing, 2025)
This study aims to analyze the effect of compensation and career development on the Quality of Work Life (QWL) among nurses at the Teaching Hospital of Syiah Kuala University. This research employed a quantitative approach with a survey method. The study involved 40 respondents consisting of civil servants and contract nurses. Data were collected using an online questionnaire with a Likert scale of 1-5 and analyzed using multiple linear regression with SPSS version 27. The results show that partially, compensation has a positive and significant effect on nurses’ Quality of Work Life with a significance value of 0.003 (<0.05). Similarly, career development has a positive and significant effect on Quality of Work Life with a significance value of 0.001 (<0.05). Simultaneously, compensation and career development have a significant effect on Quality of Work Life (F-value = 10.049; significance <0.001). These findings confirm that fair compensation systems and equitable career development programs can improve nurses’ work-life quality at the Teaching Hospital of Syiah Kuala University. It is recommended that hospital management regularly review compensation policies and expand career development opportunities to create a more productive, fair, and human-centered work environment.